Peran Pelayanan Bimbingan Dan Konseling Dalam Pendidikan Transformatif - Carles, Eko; Effendi, M. Supperapto; Hiptraspa, Zepri; Warsah, Idi; Morganna, Ruly (Islamic Counseling: Jurnal Bimbingan Konseling Islam, 2025)
This study aims to determine the Role of Guidance and Counseling Services in Transformative Education, which includes challenges for guidance and counseling in the world of education. This research was conducted as a series of collection, processing and analysis of written literature to investigate the role of guidance and counseling services in transformative education. therefore this research is called library research research results, counselors face the challenges of digital change and cyberspace. The situation of the 21st century challenges educators to be ready to work with diverse circumstances and diverse parties in the preparation of students who have different characters. The role of career guidance is to guide students to have good character and be independent, and to instill responsibility in the soul. learners. The use of technology is one of the innovations of counseling guidance where online counseling has been applied since the benefits of the internet have been felt, then counseling can be done through cyber counseling, that there are limitations in the implementation of guidance and counseling services that hinder the implementation of guidance and counseling. These obstacles can come from within (internal) or from outside (external) counselor. Regarding the constraints in the implementation of group guidance services, the internal and external constraints of the counselor are explained.